A brief history of the age of steam The power that drove the Industrial Revolution - Crump, Thomas (Robinson, 2007)
Covers the real story behind the Industrial Revolution. This title reveals not just the lives of the great inventors such as Watts, Stephenson and Brunel but also tells a narrative that reaches from the US to the expansion of China, India and South America and shows how the steam engine changed the world.